Harvey, David El Nuevo Imperialismo. Madrid, Akal Ediciones, 2004 (175 p.) ISBN: 8446020661 ISBN-13: 9788446020660 - Cobos Fontana, Mabel (Estudios Avanzados, 2013)
Harvey, David El Nuevo Imperialismo. Madrid, Akal Ediciones, 2004 (175 p.) ISBN: 8446020661 ISBN-13: 9788446020660